PERAN KANTOR URUSAN AGAMA (KUA) DALAM MENINGKATKAN FUNGSI MASJID DI LINGKUNGAN KUA KECAMATAN MEDAN DENAI - M.Husein Ritonga; Cici Khairani Sitorus; Pauzia Syahmira; Siti Ade Mustika Putri Simbolon; Nurliana Damanik (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role of the Office of Religious Affairs (KUA) in enhancing the functions of mosques in Medan Denai District, focusing on social and economic empowerment of the community. As a government institution at the sub-district level, KUA plays an important role in coordinating and facilitating mosques to function not only as places of worship but also as centers of empowerment that benefit the community. The research method used is descriptive with a qualitative approach, involving interviews with mosque administrators, KUA staff, and the surrounding community. The findings show that KUA acts as a facilitator and coordinator, connecting mosques with various social institutions to implement community empowerment programs, such as skills training, mosque financial management, and health programs. Additionally, KUA supports the development of social networks around mosques, which strengthen solidarity and cooperation among residents. In conclusion, the role of KUA in mosque management is crucial to ensure that mosques effectively carry out their social, religious, and community empowerment functions, leading to a positive impact on the well-being of the community in Medan Denai District.